System response analysis & controller design of the front adjustable suspension system of Waja using matlab simulink / Rais Hamimi Mohd Ali. - Mohd Ali, Rais Hamimi (2009)
The main purpose of this project is to maximize the car's handling and braking for good active safety and driving pleasure, and keeping vehicle occupants comfortable and reasonably well isolated from road noise, bumps, and vibrations. Comfort and road handling performance of a passenger car are mainly determined by the damping characteristic of the shock absorbers. Passive shock absorbers have a fixed damping characteristic determined by their design. Depending on the road excitation, however, it is desirable to adjust this characteristic to increase performance. Semi-active suspension systems offer the possibility to vary the damper characteristics along with the road profile by changing the restriction of one or two current controlled valves or by changing the viscosity of a magneto-rheological fluid. Semi-active suspensions are less complex, more reliable and it costs far less than active suspension. They do not require an external power source (e.g. hydraulic pump) and are safer because they can only dissipate energy and therefore cannot render the system unstable. The semi-active suspension system can be a good candidate for practical applications because it combines the advantages of passive and active suspension systems. The simulation process of this project will be done using MATLAB Simulink software. The block diagram based on the mathematical model is constructed and the result will be obtained by simulating the model. Analysis and controller design will be based upon the simulation. Finally, controller design based on the Skyhook control strategy will be introduce to improve the suspension system performance.